1977
DOI: 10.1113/jphysiol.1977.sp011661
|View full text |Cite
|
Sign up to set email alerts
|

A large birefringence signal preceding contraction in single twitch fibres of the frog.

Abstract: 1. When a single muscle fibre was externally stimulated to give a propagated action potential, a large decrease in light intensity was measured with the fibre positioned between crossed‐polarizers oriented at +/‐ 45 degrees with respect to the fibre axis. This large optical signal begins just after stimulation and its man phase precedes the development of positive tension. 2. The peak (or plateau) amplitude of the signal, expressed as the peak (plateau) change in light intensity, delta I, divided by the restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…It has been shown that the early large birefringence signal in field stimulated fibres follows the action potential with a constant delay (Oetliker &WSchfimperli, 1980) and that it propagates with the speed expected for the action potential in point stimulated fibres (Baylor & Oetliker, 1977 a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the early large birefringence signal in field stimulated fibres follows the action potential with a constant delay (Oetliker &WSchfimperli, 1980) and that it propagates with the speed expected for the action potential in point stimulated fibres (Baylor & Oetliker, 1977 a).…”
Section: Discussionmentioning
confidence: 99%
“…Wilska & Varjoranta, 1939;Martin, 1954). In this report, a signal is recorded which is assumed to represent a subsequent step in excitation-contraction coupling (Baylor & Oetliker, 1977 a). The exact nature of this process is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we optically monitor action potentials from contractile tissues using voltage-sensitive dyes, optical changes generally include light-scattering changes due to mechanical movement (BAYLOR and OETLIKER, 1977;VERGARA and BEZANILLA, 1976;MORAD and SALAMA, 1979;SAWANOBORI et al, 1981;KASS, 1981;HIROTA et al, 1985a). Accordingly, in a strongly beating heart stained with voltagesensitive dyes, action potential-related optical signals are often covered by a larger mechanical movement artifact.…”
Section: Optical Signals Accompanying Action Potentialsmentioning
confidence: 99%
“…In single fibres at room temperature illuminated with plane polarized light oriented at 450 to the fibre axis a transient decrease in light intensity is measured if an analyser, orientated at -45°, is placed between fibre and photodetector. This signal was named 'early large birefringence signal' (Baylor & Oetliker, 1977). Based on indirect measurements using isolated muscle components and a fluorescent probe it was suggested to reflect changes in free myoplasmic calcium by reflecting conformational changes of the sarcoplasmic reticulum (Oetliker, 1982).…”
Section: Pmentioning
confidence: 99%